The dominating influence of efficacy above management strategy in the long-term success of alien plant clearing programmes. (1st October 2020) - Cheney, Chad; Esler, Karen J.; Foxcroft, Llewellyn C.; van Wilgen, Nicola J.
Abstract: Conservation managers are required to make decisions in complex and uncertain contexts. To strengthen the robustness of conservation decisions, several approaches have been proposed to facilitate stakeholder engagement in the setting of conservation objectives and priority actions. While such processes have led to the formulation of several invasive alien plant management strategies to achieve specific objectives, the long-term consequences and trade-offs inherent in these strategies have not been tested. The performance of five of these strategies over 50 years was tested in the protected area context using empirical data from Table Mountain National Park, South Africa. A simulation model based on data for invasive Acacia species in a fire-driven ecosystem, focused on the interaction between strategy performance and clearing efficacy in achieving a management goal or reducing Acacia density to below 1 plant per hectare. At near perfect levels of clearing efficacy, all strategies converged towards reaching the management goal, while at lower efficacy levels the strategies diverged in their ability to achieve desired outcomes. Despite working across the largest area, strategies that focussed on clearing low density invasions, maintained the least area in a maintenance state over time. In contrast, strategies that focussed on a mix of post-fire, low density areas and high altitude areas cleared less area annually, but maintained a much larger area in a maintenance state. At higher levels of efficacy, strategies that return to previously worked areas were more successful than a post-fire strategy. Strategies that focused solely on securing water, performed poorly in maintaining low overall density of aliens. However, the influence of efficacy was significant and substantial and a much larger difference in area reaching the management goal was achieved by varying efficacy than varying strategy. As such, improving quality of work and implementation will have a far greater effect than which areas are prioritized or how this prioritization is done. While acacias are likely to persist in the long-term, improving work quality coupled with correct strategy selection will ensure continued gains in the area under maintenance and improved return on investment over time. Highlights: Infield clearing efficacy matters markedly more than area prioritisation strategy. The strategy achieving highest success varied over time and with efficacy level. When efficacy is known to be low, less area should be prioritized. Outcome monitoring in invasive alien plant programmes is paramount. Management quality and appropriate strategy reduces needs for increased funding.